
Re: Sum pattern
Posted:
Oct 5, 2012 2:39 AM


On Oct 3, 12:12 am, "Dave Snead"<dsne...@charter.net> wrote:
> Hi, > > I'm trying to put together a rule whose left hand side is a sum of arbitrary > length whose elements all have the same head f. > > For example: > > In[4]:= x = f[a1, s] + f[a2, s] + f[a3, s] > > Out[4]= f[a1, s] + f[a2, s] + f[a3, s] > > In[6]:= y = f[First /@ x, s] > > Out[6]= f[a1 + a2 + a3, s] > > which is what I want. > > However when I turn this into a rule > > In[7]:= z = x /. (p : Plus[__f]) > f[First /@ p, s] > > Out[7]= f[f[a1, s], s] + f[f[a2, s], s] + f[f[a3, s], s] > > Why isn't z equal to y? > How can I make this rule work? > > Thanks in advance, > Dave Snead
Your solution is almost correct, but fails since you did not take into account that both sides of your rule are evaluated before it is applied.
In[1]:= (p:Plus[__f])>f[First/@p,s] Out[1]= p__f>f[p,s]
Your rule wraps every expression with head f in another f, as you see in your output.
To prevent the evaluation, use RuleDelayed for keeping the righthand side and HoldPattern for the lefthand side:
In[2]:= x=f[a1,s]+f[a2,s]+f[a3,s] x /. (p:HoldPattern[Plus[__f]]):>f[First/@p,s]
Out[2]= f[a1,s]+f[a2,s]+f[a3,s] Out[3]= f[a1+a2+a3,s]
Fred Simons Eindhoven University of Technology

